Unusual early morning development of the equatorial anomaly in the Brazilian sector during the Halloween magnetic storm - Batista, I. S.; Abdu, M. A.; Souza, JR; Bertoni, F.; Matsuoka, M. T.; Camargo, P. O.; Bailey, G. J. (Amer Geophysical Union, 2006)
The solar events that occurred at the end of October 2003 gave rise to very strong geomagnetic disturbances that peaked twice with Dst values reaching -345 nT around 0000 UT on 30 October and -400 nT around 2300 UT, on the same day. Disturbances in several ionospheric parameters were observed over Brazil. This work will focus on the ionospheric response to the initial westward prompt penetration electric field and on the strong intensification of the equatorial ionization anomaly that occurred because of the electric field polarity reversal that followed in the early morning hours of 29 October. The F layer peak height over the equator first decreased under the strong prompt penetration westward electric field, which was followed by significant height increase under eastward electric field. We have used Sheffield University Plasmasphere Ionosphere Model (SUPIM) with an intensified westward disturbed electric field in the presunrise hours, presumably due to prompt penetration from the magnetosphere, in order to study the effect of such a field in the ionosphere. The simulation results showed that prompt penetration of magnetospheric electric fields of westward polarity to the nightside equatorial region seems to be the most probable cause of the initial F layer height decreases. The intensification of the equatorial ionization anomaly and the unusual enhancement on F layer peak density, which was not modeled by the SUPIM, are explained as caused by the strong eastward electric field that followed the initial phase in combination with a highly variable disturbed meridional/transequatorial wind system as inferred from the F2 layer peak height variations. The highly dynamic wind pattern, with a short-term response (2-4 hours), is compatible with the predictions of some previous theoretical model calculations reported in the literature.